THE EFFECT OF WORK ENVIRONMENT, WORK TRAINING AND PUNISHMENT ON WORK ACHIEVEMENT OF DPRD SECRETARIAT EMPLOYEES - Mulya Rosalia; Kelik Purwanto; Mayroza Wiska (Airlangga Journal of Innovation Management, 2021)
Human resources are a resource needed by an organization, because human resources are sources that play an active role in running of an organization and decision-making process. The existence of human resources in a company or government agency plays a very important role. By improving quality of human resources, it is expected that employees can work productively and professionally so that employee's work performance is expected to be more satisfactory according to required work standards. This study aims to determine the effect of work environment, job training and punishment on work performance of non-civil servant employees. The case study of this research is at DPRD Secretariat of Merangin Regency. The type of research used in this study is quantitative research, sample of this research is non-civil servant employees at DPRD Secretariat of Merangin Regency. This sampling uses non-probability sampling. The tool used to collect data is in form of a questionnaire consisting of 40 questions, data is analyzed using Validity Test, Reliability Test, Multicollinearity Test, Normality Test, Heteroscedasticity Test, R2 Determination Coefficient Test, Multiple Multiple Regression Analysis Test, Partial Hypothesis Testing ( T-test), Simultaneous Hypothesis Testing (F-Test). The results of this study indicate that dependent variable work environment (X1), job training (X3) and punishment (X4) have a positive and significant effect on employee performance.